Efficient Electron Transport Layer Free Small‐Molecule Organic Solar Cells with Superior Device Stability. Issue 14 (3rd March 2021) - Bin, Haijun; Wang, Junke; Li, Junyu; Wienk, Martijn M.; Janssen, René A. J.
Abstract: Electron transport layers (ETLs) placed between the electrodes and a photoactive layer can enhance the performance of organic solar cells but also impose limitations. Most ETLs are ultrathin films, and their deposition can disturb the morphology of the photoactive layers, complicate device fabrication, raise cost, and also affect device stability. To fully overcome such drawbacks, efficient organic solar cells that operate without an ETL are preferred. In this study, a new small‐molecule electron donor (H31 ) based on a thiophene‐substituted benzodithiophene core unit with trialkylsilyl side chains is designed and synthesized. Blending H31 with the electron acceptor Y6 gives solar cells with power conversion efficiencies exceeding 13% with and without 2, 9‐bis[3‐(dimethyloxidoamino)propyl]anthra[2, 1, 9‐ def :6, 5, 10‐ d ′ e ′ f  ′]diisoquinoline‐1, 3, 8, 10(2H, 9H)‐tetrone (PDINO) as the ETL. The ETL‐free cells deliver a superior shelf life compared to devices with an ETL. Small‐molecule donor–acceptor blends thus provide interesting perspectives for achieving efficient, reproducible, and stable device architectures without electrode interlayers. Abstract : Small‐molecule organic solar cells based on a new electron donor reach power conversion efficiencies exceeding 13% with and without the use of electrode interlayers, but differ strongly in stability. Surprisingly, the surface composition and morphology of the interlayers deteriorate with time even under inert conditions, reducing device performance. Without interlayers, the cells give stable high performance.